Physician practices in evaluation and treatment of patients with generalized joint hypermobility and bleeding. Issue 8 (December 2021) - Kendel, Nicole E.; O'Brien, Sarah H.; Laukaitis, Christina M.; Kumar, Manjusha; Levy, Howard P.; Jesudas, Rohith
Abstract : N/A: The association between bleeding and joint hypermobility may not be as diagnostically obvious in patients with milder connective tissue disorders. We surveyed members of the Hemostasis and Thrombosis Research Society regarding their knowledge, evaluation, and management practices in patients with generalized hypermobility spectrum disorder/hypermobile Ehlers–Danlos syndrome (hEDS) and bleeding symptoms. The objectives of this study were to (1) evaluate hematologists' diagnosis and management practices for patients with bleeding symptoms and generalized hypermobility spectrum disorder/hEDS and (2) determine future education and research priorities regarding bleeding symptoms within this population. Evaluate hematologists' diagnosis and management practices for patients with bleeding symptoms and generalized hypermobility spectrum disorder/hEDS. Determine future education and research priorities regarding bleeding symptoms within this population. A web-based survey was sent to Hemostasis and Thrombosis Research Society physician members. Physician demographics, preferred evaluation for hEDS, management of bleeding episodes, and referral patterns were collected and descriptive statistics were performed. Only two-thirds of respondents reported evaluating for hypermobility, despite all respondents being aware of the association with bleeding. There were significant variations in referral patterns for genetic counseling, diagnostic evaluation, and management of nonhematologic symptoms. There were also significant variations in reported medical homes for this patient population. Research prioritization included understanding the evolution of bleeding symptoms with age in this population as well as the development of functional tests to identify the molecular mechanism of bleeding and the development of novel hemostatic agents for this population. Results from 33 respondents show differing physician practices regarding the evaluation and management of bleeding in hypermobile patients. Many physicians suggested further research priorities to include studying the natural history of the disease and development of functional diagnostic testing as well as targeted therapeutic options in this patient population.